Using the technology theory to adoption virtual reality among university students - AlFarsi, Ghaliya; Tawafak, Raghad M.; Mathew, Roy; Malik, Sohail Iqbal; AlSideiri, Abir (International Journal of Electrical and Computer Engineering (IJECE), 2026)
Virtual reality is a technology field that has become an integral part in most areas of life. Before the 20th century, virtual reality consisted primarily of artificial illusions. Students encounter early obstacles in learning and the current virtual reality (VR) learning mechanism. The research is based on previous studies by filling in the blank by observing the problems that students were facing. The second main point of this research was unified theory using model of technology acceptance and use. This paper focuses on the adoption of a virtual reality learning model in order to improve student academic performance. The results of this paper prove that hypotheses have a positive impact on the factors to use the proposed model.